(untitled) (Bangladesh Heart Journal, 2021)
Introduction: In cardiac surgery, anaemia itself or combined with other risk factors has been found to be a major predictor for adverse outcome both preoperatively and postoperatively and even during extracorporeal circulation, but data about the specific tolerance of Coronary Artery Bypass Graft (CABG) patients for anaemia are conflicting and may in part be confounded by the effects of bypass surgery. Objectives: This study was performed in the National Institute of Cardiovascular Diseases (NICVD) to observe whether the early outcomes of Off-Pump CABG (OPCAB)were affected by pre-operative haematocrit levels. Methods: A total of 200 patients who underwent isolated OPCAB between January 2015 and December 2020 were retrospectively selected and purposively allocated into two groups: a)100 patients having preoperative anaemia and b) 100 patients without preoperative anaemia. Preoperative, per-operative and early post-operative variables were recorded, compiled and compared. Results: Preoperative characteristics were homogenously distributed between two groups other than haemoglobin level. Female patients had lower haemoglobin in each group. More patients of anaemic group required intraoperative and postoperative blood transfusion. The amount of blood loss and transfused blood products was also higher in anaemic patients. The ventilation time, length of ICU and post-operative hospital stay were significantly higher among anaemic patients. Among the post-operative complications, only the incidence of renal dysfunction was significantly higher among anaemic patients. Conclusion:This study has showed that anaemic patients undergoing OPCAB had an increased risk of postoperative adverse events. Importantly, the extent of preexisting comorbidities substantially affected perioperative anaemia tolerance. Therefore, preoperative risk assessment, optimization and subsequent therapeutic strategies, such as blood transfusion, should take into account both the individual level of preoperative haemoglobin and the extent of concomitant risk factors. Bangladesh Heart Journal 2021; 36(1) : 47-54